1996
DOI: 10.1111/j.1751-1097.1996.tb05672.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultraviolet‐B Exposure on the Resistance to Listeria monocytogenes in the Rat

Abstract: A rat infection model using the bacterial pathogen Listeria monocytogenes was employed to analyze the immunosuppressive activity of UVB radiation. Rats were exposed to suberythemal doses of UVB radiation for 5 or 7 consecutive days, using Kromayer or FS40 lamps respectively. Subsequently, the rats were infected subcutaneously or intravenously with Listeria. Exposure to UVB resulted in an increased number of bacteria in the spleen 4 days after infection. Listeria-specific lymphocyte proliferation assays as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 16 publications
1
48
0
Order By: Relevance
“…Suberythemal, distant UV exposure can inhibit specific cellular immunity to L. monocytogenes. Lymphocyte proliferation assays as well as DTH responses to Listeria particles in a rat infection model were significantly inhibited after suberythemal UV exposure (6). An increased Listeria load in the spleen and liver was observed, which indicates that the cellular immune parameters lymphocyte proliferation and DTH correlated well with impaired resistance.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Suberythemal, distant UV exposure can inhibit specific cellular immunity to L. monocytogenes. Lymphocyte proliferation assays as well as DTH responses to Listeria particles in a rat infection model were significantly inhibited after suberythemal UV exposure (6). An increased Listeria load in the spleen and liver was observed, which indicates that the cellular immune parameters lymphocyte proliferation and DTH correlated well with impaired resistance.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, UV-B exposure has been demonstrated to impair resistance to bacterial, viral, parasitic, and fungal infections. Importantly, the effects of UV are not restricted to skin-associated infections, but also to systemic (non-skin-associated) infections (3)(4)(5)(6)(7)(8)(9). Because UV-B is not able to penetrate much beyond the upper cell layers of the epidermis, UV-B-induced immunosuppression is probably mediated by these exposed cells, their products, or photoactivated factors present in the superficial layers.…”
mentioning
confidence: 99%
“…UVR-induced immunosuppression occurs via a number of different pathways that will not be discussed in detail here. Briefly, UVR exposure can cause immunosuppression by inhibiting antigen presentation, inducing the release of immunosuppressive cytokines, reducing phagocytosis by macrophages, suppressing natural cytotoxicity activity, and inducing the stress response [41,152,153]. The mechanisms of UVR-induced immunosuppression have been studied predominantly in mammals, but given that the innate and adaptive immune system of amphibians is similar to that of mammals [151], it is likely that these immunosuppressive mechanisms also occur in amphibians.…”
Section: Uvr and Biotic Factors Infectious Diseasementioning
confidence: 99%
“…In addition to locally compromising the host's defense against skin tumors, UVB-induced systemic immune suppression may influence the development and course of infectious disease. Although the evidence that this type of immune suppression occurs in humans is less compelling and still incomplete, studies with rodents have clearly demonstrated that exposure to UVB suppresses the resistance against both systemic and non-skin-associated local infections [3][4][5][6][7]. However, the mechanism by which UVB impairs the immunity to infectious disease is not known.…”
Section: Introductionmentioning
confidence: 99%